Intelligent algorithms and control strategies for battery management system in electric vehicles: Progress, challenges and future outlook - Hossain Lipu M.S.; Hannan M.A.; Karim T.F.; Hussain A.; Saad M.H.M.; Ayob A.; Miah M.S.; Indra Mahlia T.M. (Elsevier Ltd, 2023)
Advanced vehicle control systems; Automotive batteries; Charging (batteries); Controllers; Electric automobiles; Fire hazards; Global warming; Intelligent control; Battery performance; Battery storage system; Computation complexity; Control strategies; Intelligent Algorithms; Internal and external factors; Precise monitoring; Vehicle applications; Battery management systems